The Effect of Nostalgia Marketing towards Advertising Engagement (Aqua Case) - Nathasia, Ervina; Nasution, Reza Ashari (Journal of Business and Management, 2016)
Abstract.This research examines the effect of nostalgia marketing towards the advertising engagement. This study attempts to provide an insight and to contribute a research finding about the effect of nostalgia marketing towards advertising engagement. The hypotheses were tested using data collected from two experiments of nostalgic and non-nostalgic groups. Findings indicate that people who have nostalgic feeling towards the ads is engaged with the ads, measured by how they remember the message of the ads and brand image. This paper concludes with a discussion of managerial implications, limitations and directions for future research.Keywords: nostalgia marketing, advertising engagement, brand image, experimental research